ChemInform Abstract: Enantioselective Organocatalytic Fluorination‐Induced Wagner—Meerwein Rearrangement. Issue 4 (28th January 2014) - Romanov‐Michailidis, Fedor; Guenee, Laure; Alexakis, Alexandre
Abstract This novel highly enantioselective title reaction affords a wide range of fluorinated spirocyclic derivatives by using the new BINOL derived phosphoric acid (BIN).